PRODUKSI FILM DOKUMENTER “SPIRIT OF JAVA GAMELAN” - Firdaus; Wijaksono, Dimas Satrio (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
Indonesian is a nation that has a diversity of cultures. One of the performing arts is yogyakarta gamelan festival. Yogyakarta gamelan festival is a festival that is held regularly for 25 years and on an international scale to accommodate the meeting of players and lovers of gamelan music around the world. The final task work in the form of a documenter film entitled